2010 Symposium on VLSI Technology 2010
DOI: 10.1109/vlsit.2010.5556118
|View full text |Cite
|
Sign up to set email alerts
|

Efficient multi-V<inf>T</inf> FDSOI technology with UTBOX for low power circuit design

Abstract: For the first time, Multi-VT UTBOX-FDSOI technology for low power applications is demonstrated. We highlight the effectiveness of back biasing for short devices in order to achieve ION current improvement by 45% for LVT options at an IOFF current of 23nA/µm and a leakage reduction by 2 decades for the HVT one. In addition, fully functional 0.299um 2 bitcells with 290mV SNM at 1.1V and Vb=0V operation were obtained. We also demonstrate on ring oscillators and 0.299µm² SRAM bitcells the effectiveness (ΔVT versus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 0 publications
0
20
0
2
Order By: Relevance
“…The second degree of freedom is the !ength of the transistors. Un!ike the width, ап increase in !ength induces а decrease of ld,peak because of Y; h roll-off in this techno!ogy [7] while improving the Id,peak/1d,valley ratio thanks to а steeper sub thresho!d s!ope. The !ast parameter is the back-bias vo!tage.…”
Section: тне Ulp Diodementioning
confidence: 93%
See 1 more Smart Citation
“…The second degree of freedom is the !ength of the transistors. Un!ike the width, ап increase in !ength induces а decrease of ld,peak because of Y; h roll-off in this techno!ogy [7] while improving the Id,peak/1d,valley ratio thanks to а steeper sub thresho!d s!ope. The !ast parameter is the back-bias vo!tage.…”
Section: тне Ulp Diodementioning
confidence: 93%
“…The !ast parameter is the back-bias vo!tage. А high forward back-bias (FBB) allows to dramatically enhance the peak current Ьу reducing Y; h [7] whi!e preserving more or less the ratio Id,peak/1d,valley. Notice that FBB сап not take апу уа!ие for two reasons: FBB must Ье generated on-chip and FBB will Ье used to compensate the corner variations.…”
Section: тне Ulp Diodementioning
confidence: 99%
“…Thus, the thicker the buried oxide, the higher the source to drain coupling will be. Scaling down of the buried oxide is mandatory to maintain the electrostatic characteristics of MOSFETs (Figure 6(a)) [25][26][27][28]. Recent results have shown that [29,30]; (b) strained dual channel CMOS process flow [29].…”
Section: Fully Depleted Devices On Insulator Ultra-thin Silicon Thickmentioning
confidence: 99%
“…buried oxide could be scaled to 10 nm on large 300 mm diameter wafers with Si layers as thin as 6 nm [25][26][27][28]. The control of such substrates could lead to multi-threshold control.…”
Section: Fully Depleted Devices On Insulator Ultra-thin Silicon Thickmentioning
confidence: 99%
See 1 more Smart Citation